Polysaccharide-based responsive hydrogels for skin regeneration - Jha A.; Kumar M.; Bharti K.; Mishra B. (My University, 2025)
Hydrogels, which are three-dimensional polymer structures, are one of the most extensively explored platforms for applications in wound healing and skin repair. Polysaccharide-based responsive hydrogels, which act as biomaterials, are crucial in the development of regenerative medicine. Besides having advantages, such as the ability to absorb wound exudates, ensure gaseous exchange, and load and deliver multiple drugs simultaneously, hydrogels can also cause scar formation without skin appendages. Therefore, in recent years, numerous skin-regenerating hydrogel scaffolds have been reported that ensure complete scarless healing of damaged skin and topical wounds. Skin regeneration is an intricate process involving hemostasis (coagulation), inflammation (cell infiltration), proliferation (cell migration, epithelialization, angiogenesis, and granulation tissue formation), and maturation (collagen deposition or formation of scar tissue). Dressing materials based on hydrogel scaffolds that support and promote the above process can play a key role in skin regeneration. Natural polysaccharide-based hydrogels are preferable owing to their low cost, biodegradability, and biocompatibility. Polysaccharide hydrogels are usually equipped with bioactive molecules, which include stem cells, peptides, growth factors, etc., for efficient skin regeneration. This chapter discusses polysaccharide hydrogel-based dressing materials for skin regeneration. © 2024 Elsevier Inc. All rights reserved.